1977
DOI: 10.1002/cpt1977212147
|View full text |Cite
|
Sign up to set email alerts
|

Clinical eftects and pharmacokinetics of racemic methadone and its optical isomers

Abstract: The respiratory and pupillary effects of oral l-, d-, and d,l-methadone were studied in healthy male volunteers 21 to 35 yr of age. The mean half-life of drug in blood was 22 hr for racemic methadone, 24 hr for l-methadone, and 25 hr for d-methadone. The effects of d-methadone were not significantly different from the placebo response at a 7.5 mg dose, whereas a 50 and 100 mg dose slightly depressed respiration in one subject each. Both 7.5 mg of l-methadone and 15 mg of d,l-methadone induced intense and susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
1

Year Published

1980
1980
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(53 citation statements)
references
References 6 publications
4
47
1
Order By: Relevance
“…Other studies, although not as extensive as the present study, have also shown higher l-methadone plasma concentrations in subjects receiving d,l-methadone [9,23]. However, a study in 12 non-opiatetolerant volunteers [6] showed consistently lower l-methadone plasma concentrations in comparison with d-methadone. After changing from l-methadone to d,l-methadone on day 15, no significant changes in the l-methadone:dmethadone ratio were observed in the d,l-methadone group between day 15 and day 22.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Other studies, although not as extensive as the present study, have also shown higher l-methadone plasma concentrations in subjects receiving d,l-methadone [9,23]. However, a study in 12 non-opiatetolerant volunteers [6] showed consistently lower l-methadone plasma concentrations in comparison with d-methadone. After changing from l-methadone to d,l-methadone on day 15, no significant changes in the l-methadone:dmethadone ratio were observed in the d,l-methadone group between day 15 and day 22.…”
Section: Discussioncontrasting
confidence: 48%
“…Sullivan et al [5] suggested that d-methadone metabolites may have an analgesic effect. In a study using 30 healthy, non-opiate-tolerant volunteers, Olsen et al [6] found similar respiratory and pupillary effects using a 7.5-mg l-methadone dose and a 15-mg d,lmethadone dose. One subject showed slightly depressed respiration on high-dose d-methadone but the changes induced by l-methadone were of longer duration than those of d,l-methadone.…”
Section: Introductionmentioning
confidence: 81%
“…Thus, a significant overestimation incidence of nausea and vomiting. This was surprising as others have not reported such a finding [34].…”
Section: Pharmacokineticsmentioning
confidence: 80%
“…Thus, a 50% reduction in inhibition is caused by the isomer that possesses most of the analgesic action of methadone [34] and antiaddictive action [24]. In fact, the r -methadone has a 10-fold higher affinity at the µ- and δ-opioid receptors and possesses up to 50 times the analgesic activity of s -methadone in human and animal models [1, 23, 35]. Fortuitously, the r -isomer would thus possess half the potential to prolong the QT, while twice the potency of the r/s -mixture in terms of analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…1) with known r- and s -isomers [23, 24]. Methadone prolongs the QT interval on the electrocardiogram [25,26,27,28] due to methadone’s known inhibition of the rapid potassium-rectifying channel IKr [29,30,31].…”
Section: Introductionmentioning
confidence: 99%